Investigation into voltage and angle stability of a hybrid HVAC-HVDC power network - Azimoh, Leonard Chukwuma (Department of Electrical Engineering, 2016)
This study investigates the power stability problems of HVDC and VSC-HVDC interactions on their hybrid networks with HV AC link, with the intention of bringing out their weaknesses and strengths. The knowledge of this will assist network planners to be informed on ways of improving the efficiency and quality of power systems network. The simulations for this study was done using DIgSILENT Powerfactory software version 14.0.515. This study encapsulates the three major stability problems affecting power systems network, namely, the voltage stability, transient stability and small signal stability. The voltage stability study was conducted using series of load flows at various levels to plot the VP and QV curves, and the results were used to analyze the systems proximity and sensitivity to voltage collapse, as well as the maximum loading point (MPL) of the network. Furthermore, the voltage angle, and terminal voltage responses during a three-phase short circuit disturbance was also used to analyze the voltage stability of the networks. For the transient stability study, several case studies were investigated and their dynamic performances during three-phase short circuit perturbations were analyzed. The small signal stability investigation was done using modal analysis to determine the small signal stability of the three transmission schemes mentioned above. The transient and small signal stability, which are both subsets of rotor angle stability, were further investigated to show the effect of power systems stabilizer (PSS) and automatic voltage regulator (A VR) on rotor angle stability. The results of the analyses show that the HVDC transmission scheme provides the best alternative for bulk power transmission over a long distance. The VSC-HVDC transmission network is suitable for interconnections where the tie with HV AC networks have a low short circuit ratio (SCR). Other conclusions reached with the investigations are explained in chapter ten.